(untitled) (Altre Modernità, 2013)
The essay, based on material that is for the most part unpublished, conserved in the Biblioteca Nazionale Braidense and in the Archivio di Stato in Milan, re-constructs, through the events of the Società Patriotica founded by Maria Teresa in 1776 in Milan, the characteristics, modalities and results in the activity going on inside the society in the transferring of plants sector, in the last decades of the 18th Century. It opens with an analysis of the long and the painstaking work of the naturalists and the illuminated aristocrats gathered in the society, that brought to life a new kind of transferring, based no longer, as in previous centuries, on the occasional initiative of a few persons, but on a rational and programmed piece of work that even today constitutes, though in a widely different way, the point of departure for the scientists that operate in this sector. It proceeds then in examining the importance and at the same time the difficulties, the uncertainties, the waiting times, the delays and the frequent negative outcomes in the transferring of plants and the informations necessary for the experiments made on them in botanical gardens before being cultivated in the open field. Finally it concludes with the specific analysis of certain plants transferred successfully, that today, are still part of the Lombard landscape, such as the olive tree, the hard wheat, the potato.